(untitled) (Conferencea, 2023)
One of the important problems of modern otorhinolaryngology is the problem of hearing pathology in children with type 1 diabetes mellitus. Arising in early childhood, acute purulent otitis media (APOM) often becomes recurrent and turns into a chronic form. This is due to the fact that the main indicators of the immune system in children with type 1 diabetes mellitus with APOM at an early age are violated. The purpose of our work is to study the indicators of cellular-humoral immunity in young children suffering from OCD. Under our supervision in the ENT department of the regional children’s hospital of Bukhara there were 32 children with APOM: under the age of 6 months -7, from 6 months to 1.5 years - 11, from 1.5 to 3 years -14. was determined by the E-ROCK method, B- lymphocytes by the EFS-ROCK method. The state of humoral immune status: the content of T-lymphocytes was determined by the E-ROCK method, B- lymphocytes by the EFS-ROCK method. The state of humoral immunity was assessed by the level of serum immunoglobulins in blood plasma. For quantitative determination of immunoglobulins of classes A, M, G, in blood serum, the method of simple radial immunodiffesis according to Mancini was used. The phagocytic activity of neutrophils was determined using a latex test. The control group (donors) consisted of 30 practically healthy children of the same age and gender.